Indian Agency in Spanish Florida: Some New Findings from Mission Santa Catalina de Guale - David Hurst Thomas (Journal of Global Initiatives, 2011)
The resurgence of Spanish mission archaeology in the American Southeast over the last three decades demonstrates the fallacy of the rigid and misleading Borderlands perspective on Franciscan-American Indian interactions. While engaging in the archaeology of Mission Santa Catalina de Guale, I suggested a broader-based,"cubist" approach toward the Spanish Borderlands history to seek, "multiple, simultaneous views of the subject" (Thomas 1989:7). Archaeology can indeed provide a critically important window through which to glimpse the Native American and European interactions in the Borderlands as elsewhere. By "democratizing" the past, archaeologists are framing new perspectives on minority populations and their experiences with dominant colonial cultures (Deagan 1991; Lightfoot 2005:17).